Depression and anxiety in inflammatory bowel disease: mechanisms and emerging therapeutics targeting the microbiota-gut-brain axis - Qian, Yan; Chen, Yang; Liu, Linquan; Wu, Tiesong; Chen, Xiehui; Ma, Guiping (Frontiers in Immunology, 2025)
Inflammatory bowel disease (IBD), encompassing ulcerative colitis (UC) and Crohn’s disease (CD), represents a group of chronic, relapsing intestinal inflammatory disorders with incompletely understood etiology. Depression and anxiety, as prevalent psychiatric conditions, exhibit rising incidence rates; notably, IBD patients demonstrate heightened susceptibility to these disorders compared to the general population, thereby exacerbating disease burden and increasing risks of adverse clinical outcomes. Emerging evidence reveals shared pathophysiological mechanisms between IBD and depression/anxiety. This review specifically addresses depression and anxiety within the IBD disease context, integrating recent epidemiological evidence and risk factors. Centered on the gut-brain axis framework, we examine mechanistic underpinnings through two interconnected pathways: gut dysbiosis and neuroimmune interactions mediated by inflammatory cytokines and neurotransmitters. Finally, we explore therapeutic interventions for depression and anxiety in IBD based on these mechanistic insights, aiming to advance clinical and public health management strategies.